Development of an algorithm for effective management of the technological process of the industrial enterprise based on the programmable logic controller TM171PDM27S Schneider Electric - V. R. Ivanovа; V. V. Novokreshenov; N. V. Rozhencova (Известия высших учебных заведений: Проблемы энергетики)
Ventilation and air conditioning systems are necessary to regulate air exchange, maintain temperature and humidity, and provide a comfortable microclimate. Their installation is certainly relevant in premises for various purposes: at industrial facilities, in residential buildings, in administrative institutions, warehouses and others. In order to effectively carry out and ensure the proper functioning of ventilation, it is necessary to introduce automated control schemes for the operation of these systems, as well as the use of various modern equipment (ventilation units, ventilation units, silencers, air filters, air heaters, etc.) to increase the reliability of airspace cleaning and the cost-effectiveness of manufacturing the system generally. The paper presents the scheme and algorithm for the effective control of the technological process of the ventilation system of an industrial enterprise based on the TM171PDM27S Schneider Electric programmable logic controller. The analysis of existing ventilation systems is carried out, the description of ventilation systems is presented, the stand's appearance is presented, the choice of a programmable logic controller is justified, methodological recommendations for acquiring programming skills using the EcoStruxure Machine Expert - HVAC environment are presented, automatic control of the supply ventilation system for the foundry of an industrial enterprise is organized goals of a visual study of elements of ventilation systems, methods of regulation and control of parameters in ventilation systems. The main goal of creating a training stand is to study the settings and operating modes of automated ventilation and air conditioning control systems. In the course of further improvement of the circuit, classes of the following nature are possible: determination of the static and dynamic characteristics of the fan; study of the characteristics of an automated damper; pressure regulation by controlling a fan, etc.